2014
DOI: 10.3389/fmicb.2014.00516
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial community composition altered by increased nutrient availability in Arctic tundra soils

Abstract: The pool of soil organic carbon (SOC) in the Arctic is disproportionally large compared to those in other biomes. This large quantity of SOC accumulated over millennia due to slow rates of decomposition relative to net primary productivity. Decomposition is constrained by low temperatures and nutrient concentrations, which limit soil microbial activity. We investigated how nutrients limit bacterial and fungal biomass and community composition in organic and mineral soils within moist acidic tussock tundra ecos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
113
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(136 citation statements)
references
References 97 publications
20
113
3
Order By: Relevance
“…Bacterial community shifts may be resulting in potentially altered substrate use preference by decomposers, as well as different genetic functional activity. This is supported by other studies from Arctic soil and permafrost ecosystems that provide evidence of altered microbial community composition and rapid functional response to temperature manipulations, thawing soils, or fertilization treatments (Deslippe et al, 2012;Koyama et al, 2014;Mackelprang et al, 2011). For example, Actinobacteria abundance was found to increase in response to both increased temperature (Deslippe et al, 2012) and in freshly thawed permafrost soils (Mackelprang et al, 2011), similar to the response we observed in the Deep zone (Fig.…”
Section: Bacterial Community Shiftssupporting
confidence: 77%
See 1 more Smart Citation
“…Bacterial community shifts may be resulting in potentially altered substrate use preference by decomposers, as well as different genetic functional activity. This is supported by other studies from Arctic soil and permafrost ecosystems that provide evidence of altered microbial community composition and rapid functional response to temperature manipulations, thawing soils, or fertilization treatments (Deslippe et al, 2012;Koyama et al, 2014;Mackelprang et al, 2011). For example, Actinobacteria abundance was found to increase in response to both increased temperature (Deslippe et al, 2012) and in freshly thawed permafrost soils (Mackelprang et al, 2011), similar to the response we observed in the Deep zone (Fig.…”
Section: Bacterial Community Shiftssupporting
confidence: 77%
“…Mackelprang et al (2011) also reported varying shifts in a wide array of functional genes in response to permafrost thaw. In addition, Koyama et al (2014) documented a decrease in the oligotrophic Acidobacteria phylum in response to fertilizer soil inputs which they attributed to be a direct result of competition with copiotrophic α-, β-, and γ -Proteobacteria which increased in abundance with fertilizer treatment. While oligotrophic organisms such as Acidobacteria are adapted to survive in low nutrient environments, they are often outcompeted in more fertile soils by generalist copiotrophs (such as Proteobacteria), which are better equipped to harvest available nutrients.…”
Section: Bacterial Community Shiftsmentioning
confidence: 99%
“…Our results stand in contrast to negative relationships between bacterial diversity and N additions reported from previous studies conducted at individual sites (19,43). This finding points to the importance of local context and highlights the pitfalls associated with extrapolating results obtained from individual sites to other ecosystems or soil types.…”
Section: Resultscontrasting
confidence: 56%
“…Interestingly, cold adapted Burkholderia species have also been recovered from coastal regions of the Ross Sea in Antarctica [27]. Copiotrophic a-and b-Proteobacteria were more responsive to shifts in nutrient status in Arctic soils than other taxa [28], supporting their proposed role as keystone taxa. Whether similar microbial community structural changes might be expected in oligotrophic Antarctic desert soils remains uncertain.…”
Section: Microbial Diversity In Cold Environmentsmentioning
confidence: 91%